THE RELATIONSHIP BETWEEN ECONOMIC GROWTH AND MIGRATION IN TERMS OF 14 EUROPEAN UNION COUNTRIES AND TURKEY - Hasan Yavuz; Agnieszka Parlinska (Polityki Europejskie, Finanse i Marketing)
Efforts to get rid of poverty cause migration movements that have consequences not only for themselves, but also for future generations. Migration movements affect many economic variables such as human capital, demand, supply, the balance of payments, income distribution, wage level, and national income. The literature on migration is often studied in the economic, political and security fields. This study focuses on the relationship of migration with economic growth. There are studies that determine two-way causality in the relationship between economic growth and migration. It is seen that the country groups specified here can explain these different results. In this study, our purpose is to investigate whether international migration affects the economic growth of the receiving country. Therefore, the actual relationship between migration and the eco- nomic growth rate in terms of economic size using 14 similar European Union countries and Turkey for the period 1978-2019 (with panel data analysis) was tested. It is seen that the test results explain the positive effects of migration in accordance with the literature.